COMPOSTING OF HOUSEHOLD WASTES IN CONTAINERS (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2005)
Household wastes handling improperly leads to increasing of total amount of wastes deposited in landfills. Investigations of family (3 adults and 3 children) during 3 year period appeared, that average weight of kitchen wastes produced was 62,2 kg per habitant in year. Kitchen wastes have high moisture content 70 – 90% and high density 500 – 600 kg/m³. Investigated weight of liquid leached was 43,2%, if the kitchen wastes were composted without additional material and leakage was 15,4% if wastes was composted together with 10% dry bulking materials (straw5% + sawdust5%). Leakage was not observed, if kitchen wastes were co-composted with 25% lake rootfelt. Maximal temperatures in 1,2 m3 container were 36 °C for compost of weeds and 61 °C for screened weed’s compost. Non-treated with etch wheat grain’s sprouts all perished after 40-day couching period in compost having maximal temperature 36°C during previous composting process and in same time survived 75% of sprouts in compost having maximal temperature 61 °C during previously performed composting process.